Sifat Pemesinan Lima Jenis Kayu Kurang Dikenal - Achmad Supriadi (Jurnal Ilmu Pertanian Indonesia, 2017)
This paper deals with a study in machining properties of five wood species, i.e. marasi (Hymenaea sp.), asam jawa (Tamarmaus indica), ki keuyeup (Enonimus javanica), cantigi (Pempis acidula), and Kendal (Euretia acuminate R.) from West Java. The result revealed that planing, shaping, boring, turning, and sanding properties were significantly affected by wood species. The machining qualities of asam jawa, marasi and ki keuyeup woods with respect to criteria were good to very good, while those cantigi and Kendal fair to good. There is a tendency of the higher density of wood, the better of machining properties. These five of wood can be suggested to be processed into various products processing with machining results as good to very good, except cantigi and kendal if need turning process must be done more carefully.